Prevalence of Post Tonsillectomy Haemorrhage in Universal College of Medical Sciences Teaching Hospital - Bishow Tulachan; Roshan Acharya; Savita Aryal; Himal Poudel; Bisesh Regmi; Manoj Rimal; Bhuwal Agrahari (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Tonsillectomy is one of the common surgeries for different indications performed by the Otolaryngologists globally. Despite enriched with the several techniques and new equipments, the patients are still not free of major complications like haemorrhage post surgery. Hence, the study is aimed to determine the prevalence of haemorrhage following tonsillectomy. MATERIAL AND METHODS A retrospective study was carried out reviewing the medical records of all tonsillectomy patients operated in Universal College of Medical Sciences-Teaching Hospital (UCMS-TH) from July 2019 to Januray 2025. 200 patients' ﬁles were reviewed but only 187 were included due to lack of information. All cases were done under general anaesthesia. Cold dissection plus bipolar diathermy and bipolar diathermy only were used during the surgery. Number of post tonsillectomy haemorrhage were noted irrespective of the duration. Data were entered in MS-Excel 2007 and analyzed in rate and percentage. RESULTS Six (3.2%) out of 187 patients had post tonsillectomy haemorrhage (PTH). It was seen in 16-55 years age groups ( 2 males and 4 females) and were operated for recurrent tonsillitis. It occurred between ﬁfth-tenth post operative day. CONCLUSION The prevalence of post tonsillectomy haemorrhage (3.2%) was low compared to other centers. Both the genders were affected and principally seen on recurrent tonsillitis cases. Although a life threatening condition, it can be managed safely.